Perfil clínico de pacientes portadores de esclerose lateral amiotrófica acompanhados em centros de referência de Belo Horizonte, MG - Laura de Godoy Russeff Prado (2015)
Objective: to systematically analyze the first series of cases of amyotrophic lateral sclerosis (ALS) in Minas Gerais; verify possible associations between neuropsychiatric symptoms and clinical course of the disease. Method: This is a cross-sectional and descriptive study of a consecutive series of patients with probable or defined sporadic ALS according to Awajis criteria, followed at two referral centers of Belo Horizonte: Hospital das Clínicas/UFMG and at Hospital Júlia Kubitschek/FHEMIG. Patients underwent clinical, functional, psychiatric (anxiety and depression questionnaires), and a brief cognitive research (Mini-Mental State Examination, Montreal Cognitive Assesment). Comparisons of patient subgroups were made and correlations between clinical features, functional, psychiatric and cognitive parameters were investigated. Results: Of the 61 enrolled patients, 38 cases (62.3%) were male, resulting in a male/female ratio of 1.6:1. The mean age at onset of symptoms was 54.9 years (SD ± 11.4). The mean age at diagnosis was 56.3 years (SD ± 11.1) and the average time to obtain the diagnosis was 1.7 years (SD ± 2.0). The average age at assessment was 58.6 years (SD ± 10.7). Regarding the initial form of presentation, six cases (9.8%) were bulbar, 43 cases (70.5%) were spinal and 12 cases (19.7%) were generalized. Anxiety was found in 18 patients (29.5%) and depression in 20 patients (32.8%). When comparing patients with and without depression, there was significant difference regarding symptoms of anxiety (p <0.001). There was no difference in relation to disease duration, functional scale score or on cognitive tests. A positive correlation between anxiety and depressive symptoms was found (p <0.001). Conclusion: in general the profile of this sample is similar to other national and international series. The knowledge of the profile of our patients is the first step to improve the quality of our services and provide essential data for further studies.